واقع جودة الخدمات الصحية في الجزائر بين الإنجازات والتحديات - زمورة, نزيهة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تهدف هذه الدراسة إلى تسليط الضوء على موضوع جودة الخدمات الصحية في الجزائر ، نظرا لأهمية الجودة في الرعاية الصحية، خاصة وأنها تهتم بصحة المريض وتسهر على راحته، و يبقى ذلك مرهون بالآليات البشرية والمادية المعتمدة، سواء في تحقيق الجودة أو القضاء على المشاكل والتحديات التي تواجه الخدمة والرعاية الصحية، خاصة وان النظام الصحي متكامل وشامل وأي خلل يهدد نشاط معين سيلحق الضرر ببقية العمليات وسينعكس ذلك بطبيعة الحال على المريض، لذا لا بد والتكيف مع المستجدات و التغيرات الحاصلة سواء في البيئة الداخلية أو الخارجية للقطاع الصحي، مع التصدي لمختلف التحديات والأوبئة والأمراض التي تهدد جودة الخدمة الصحية من جميع الجوانب التنظيمية والتسييرية والصحية. Abstract: This study aims at highlighting the topic of health services quality in Algeria due to its importance in health care as quality offers convenience and comfort for patients. However, maintaining quality or eliminating service and health care constraints and challenges remains contingent on the adopted human and financial mechanisms. Besides, the health system must be adapted to the latest developments and changes in or out of the health sector. Because this system is integrated and inclusive and any malfunction in a particular activity may negatively affect other processes, and which will be of course reflected on the patient. Moreover, various challenges, epidemics and diseases that threaten the quality of health service should be addressed from organizational, managerial and health aspects.